L1 adaptive output regulator design with application to Managed Pressure Drilling. (June 2016) - Mahdianfar, Hessam; Hovakimyan, Naira; Pavlov, Alexey; Aamo, Ole Morten
Abstract : Highlights: A modification to L 1 adaptive control that allows for disturbances entering at the output is presented. A systematic filter design procedure based on LMIs is provided. The developed control strategy is applied to Managed Pressure Drilling with harmonic disturbances representing the heave motion of a floating drilling rig. A black-box model for modeling the flow dynamics and surge and swab pressures in a medium size test facility is developed using standard system identification techniques. The experimental results of control system tests in the test facility are presented. Abstract: This paper presents a modification to L 1 adaptive control that allows for disturbances entering at the output and application of this control strategy to Managed Pressure Drilling with harmonic disturbances representing the heave motion of a floating drilling rig. By incorporating the disturbance at the output into the closed-loop reference model, it is shown that the L 1 adaptive control structure can be left unchanged while the original transient performance bounds are preserved. It is further shown that rejection of the output disturbance can be taken care of entirely in the filter design step of L 1 adaptive control using the internal model principle. A systematic filter design procedure based on LMIs is provided, that requires only one tuning parameter to be adjusted by the designer. The control design is applied to disturbance attenuation and set-point tracking in the so-called heave problem in oil well drilling. We present experimental results of control system tests in a medium size test facility emulating a 900 m long well.